Bibliometric Analysis of the Development of Information Literacy Publications in ASEAN Countries Indexed by the Lens Database - Yani, Luthfiyah Eka; Kangko, Danang Dwijo; Kurnianingsih, Indah; Maulana, Aya Yahya (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2025)
Background: Information literacy plays a vital role in supporting education, research, and informed decision-making in the digital era. In the context of ASEAN countries, the development and dissemination of research on information literacy contribute to regional knowledge-sharing and capacity building. However, comprehensive mapping of scholarly output on this subject in ASEAN remains limited, especially those indexed in global academic databases.Objective: This research aims to map and analyze scientific publications on the subject of information literacy in ASEAN countries indexed by the Lens database. The analysis focuses on co-occurrence and co-authorship networks using VOSviewer, as well as determining author productivity, publication trends, and institutional and national contributions to the development of information literacy scholarship.Methods: A bibliometric analysis approach was applied using data extracted from the Lens database. Microsoft Excel and VOSviewer software were utilized to clean the data and generate visualizations. Co-occurrence analysis was used to identify thematic trends, while co-authorship analysis revealed collaboration networks. The study also examined publication growth by country and institutional affiliation from 1998 to 2023.Results: A total of 504 articles related to information literacy were initially retrieved from the Lens database. After data cleaning, 469 relevant articles remained. Among the 10 ASEAN countries, only 6—Indonesia, Malaysia, Singapore, the Philippines, Thailand, and Vietnam—have publications on this subject indexed in the Lens database. Key emerging topics in recent years include data collection techniques, information needs, documentation, public observation, communication, and human resources. Shaheen Majid emerged as both the most productive author and the one with the strongest collaboration network. The study shows a general upward trend in publication numbers over the 1998–2023 period.Conclusion: Scientific publications on information literacy in ASEAN countries have shown significant growth over the past two decades. Collaborative research networks among authors play an important role in enhancing productivity. These findings highlight the need for greater collaboration and capacity building across ASEAN member states to strengthen regional contributions to the field of information literacy.